Effects of regular exercise on ischemia-modified albumin and total sulfhydryl levels in young women: a cross-sectional study - Bilici, Ömer Faruk; Kahraman, Muhammed Zahit; Türker, Ali; Seyhan, Sinan; Sahin, Mehmet Furkan; Demir, Halit; Acar, Görkem; Bilici, Muhammed Fatih; Soylu, Caglar; Söğüt, Tarkan; Bakum, Abdullah (Frontiers in Physiology, 2025)
BackgroundRegular physical activity provides systemic health benefits, including improvements in redox homeostasis and antioxidant defense. Ischemia-modified albumin (IMA) and total sulfhydryl groups (–SH) serve as sensitive biomarkers of oxidative protein modification and thiol-dependent antioxidant capacity. However, evidence regarding their relationship in young women who participate in structured exercise remains limited. This study aimed to investigate associations between regular exercise and serum IMA and –SH concentrations in healthy young women to better understand potential exercise-related redox differences and sex-specific physiological profiles.MethodsThis cross-sectional study included 30 healthy women aged 18–25 years, recruited from university campuses and local fitness facilities. Participants were assigned to an exercise group (n = 15), performing structured training ≥3 sessions per week for at least 1 year, or a sedentary control group (n = 15) with no structured exercise history. After ethical approval and informed consent, venous blood samples were drawn following overnight fasting. Serum IMA was measured using the albumin–cobalt binding assay, while –SH concentrations were determined via the Ellman method. All analyses were conducted in duplicate under standardized laboratory conditions. Independent samples t-tests and Cohen’s d effect sizes with 95% confidence intervals were calculated.ResultsBaseline anthropometric variables (age, height, weight) did not differ significantly between groups (p > 0.05). Serum IMA levels were significantly higher in the exercise group than in controls (0.75 ± 0.09 vs. 0.61 ± 0.08 ABSU; p < 0.001; d = 1.65). Conversely, –SH concentrations were significantly lower among exercising women (0.370 ± 0.046 vs. 0.447 ± 0.036 mmol/L; p < 0.001; d = −1.88). Both biomarkers showed very large effect sizes, reflecting robust differences in oxidative stress and antioxidant defense associated with regular physical training.ConclusionThis cross-sectional analysis indicates that regular structured exercise in young women is associated with a distinct redox profile characterized by elevated IMA and reduced –SH levels. This dual pattern may reflect altered redox homeostasis with increased oxidative protein modification and greater thiol utilization. IMA and –SH appear to be complementary biomarkers for evaluating exercise-related redox responses. Future longitudinal studies are needed to establish causal mechanisms and clinical significance.Clinical Trial RegistrationRegistered at ClinicalTrials.gov (NCT07181044) on 6 September 2025.